Profitability Determinant and the Effect of Capital Structure - Eny Maryanti; Dewi Ratiwi Meiliza (Journal of Economics, Business, and Government Challenges, 2020)
The purpose of this study is to verify the effect of company growth, sales growth, company size and profitability towards capital structure. The population uses manufacturing companies with purposive sampling technique and obtained a sample of 30 companies. The result of the research indicates that the variable of Company Growth and Company Size have not effect significantly towards profitability. Whereas Sales Growth variable have effect significantly towards profitability. Profitability, sales growth, and company size variables have not effect towards capital structure whereas the growth of the company have effect to the capital structure.